EM-Based Monitoring and Probabilistic Analysis of Prestress Loss of Bonded Tendons in PSC Beams - Zheheng Chen; Shanwen Zhang (Advances in Civil Engineering)
The prestress level is a key factor of prestressed concrete (PSC) beams, affecting their long-term serviceability and safety. Existing monitoring methods, however, are not effective in obtaining the force or stress of embedded tendons. This paper investigates the feasibility of elastomagnetic (EM) sensors, which have been used for external tendons, in monitoring the long-term prestress loss of bonded tendons. The influence of ambient temperature, water, eccentricity ratio, plastic duct, and cement grouts on the test results of EM sensors is experimentally examined. Based on the calibrated EM sensors, prestress loss of a group of PSC beams was monitored for one year. In order to further consider the high randomness in material, environment, and construction, probabilistic analysis of prestress loss is conducted. Finally, the variation range of prestress loss with a certain confidence level is obtained and is compared with the monitored data, which provides a basis for the determination of prestress level in the design of PSC beams.